Analysis of Village Governance in the Poverty Alleviation Program: A Case Study of Village in Sinjai Regency - Adi Nawir; Ashar Abdillah; Jusniaty Jusniaty; Muhammad Lutfi; Faiz Fakhruddin (Journal of Governance, 2026)
This study aims to analyze the capacity of village governments in Sinjai Regency, focusing on Lasiai Village, in poverty alleviation. It focuses on distributional capacity, responsiveness, and the collaborative networks established within the village governance process. The study employed a qualitative approach through document analysis, observation, and in-depth interviews. The results indicate that the village government's distributional capacity has been implemented through participatory mechanisms such as village deliberations, but still faces challenges related to the accuracy of poverty data, thus limiting the effectiveness of aid distribution. The village government's responsive capacity is considered good, indicated by active community involvement and responsiveness to urgent needs, although adaptation to socioeconomic dynamics still needs to be strengthened. Furthermore, collaborative networks with various parties, including government agencies, village facilitators, and community organizations, have positively contributed to the provision of resources and technical support for poverty alleviation programs. Overall, the Lasiai Village Government's capacity in distributional capacity, responsiveness, and collaborative network aspects demonstrates quite good performance. However, improvements in data quality, service innovation, and strengthened collaboration with various institutions are still needed to support effective poverty alleviation.